RELATO DE UMA VIAGEM TURISTÍCA-COMERCIAL ATRAVÉS DA DIVERSIDADE CULTURAL, SOCIAL E DEMOGRÁFICA CALIFORNIANA - Cícera Rodrigues Yoshimoto (Universidade do Oeste Paulista, 2007)
This article aims to narrate a tourist-commercial trip through cultural, social and demographic diversities. The top point of the trip was the camper as a mean of transportation to explore the North of California, followed by American family hospitalities who host the Brazilian exchange students.